"The Only Thing Red About Her": Personal Intertextual Palimpsests in Lucille Ball's HUAC Testimony. Issue 4 (2nd October 2021) - Barnes, Nicole Williams; Palczewski, Catherine Helen; Lund, Heather Nicole
Abstract: Lucille Ball's 1953 testimony to the House Un-American Activities Committee is a rhetorical puzzle. How was a woman with documented Communist affiliation able to avoid being blacklisted? The intertextual conflation of Lucille Ball with Lucy Ricardo provided resources to answer the charge against her and transform the conversation from one of anti-American threats to the republic to one of personal familial duty and responsibility. We argue that only through an intertextual reading of Ball's testimony can rhetoricians understand its effectiveness. We analyze the text of her September 1953 HUAC testimony alongside episodes of I Love Lucy to reveal a Lucy Ricardo/Lucille Ball palimpsest and reveal how Ball made her innocence-because-of-feminine-ignorance argument achieve narrative fidelity and probability. The case also presents an interesting example of where a retreat from the political to the personal served to thwart public persecution for political actions.